Mixed Economy of Welfare Emerging in Poland: Outplacement and Non-Governmental Employment Agencies Examples - Andrzej Klimczuk (E-Journal of International and Comparative Labour Studies, 2015)
One of the key challenges of social policy in Poland in the early 21st century is to adapt its management to the requirements of a service economy. Essential conditions for the mixed economy of welfare have been already created after adjustments of the subsystems of national social policy during the first years of membership in the European Union since 2004. Labour market policies (LMPs) already include the relationships between providers from the public sector, the commercial sector, and the non-governmental sector. However, the tasks and services of individual entities and institutions still lack coordination and integration. This paper focus on the examples of possibilities for their development by combining the activation (enabling) policy with concepts of the governance and welfare mix. The paper presents the results of the author's research on the implementation of welfare mix solutions in the field of professional activation of the unemployed people in Poland. Two case studies are included (1) the implementation of outplacement programs that are based on the cooperation between different entities; and (2) the cooperation between the public employment services and non-governmental employment agencies in the activation of people with disabilities in the labour market. Moreover, basic concepts of ongoing reforms of active labour market policies (ALMPs) in Poland were discussed. The summary contains the practical recommendations and possible directions for further research in the field of integration of employment services.
Keywords: E24; J14; J28; J24; J6; Z1; 330; activation policy; cross-sectoral cooperation; disability; employment agencies; labour market policy; local partnerships and pacts; outplacement; unemployment; mixed economy of welfare; welfare mix; Non-governmental organization; Employment